An Introduction to Aquatic Toxicology - Nikinmaa, Mikko (Elsevier Science, 2014)
An Introduction to Aquatic Toxicology is an introductory reference for all aspects of toxicology pertaining to aquatic environments. As water sources diminish, the need to understand the effects that contaminants may have on aquatic organisms and ecosystems increases in importance. This book will provide you with a solid understanding of aquatic toxicology, its past, its cutting-edge present and its likely future. An Introduction to Aquatic Toxicology will introduce you to the global issue of aquatic contamination, detailing the major sources of contamina.